(untitled) (African Journal of Dairy Farming and Milk Production, 2019)
A total of forty Arsi-Bale male goats weighing on average (±SE) 16.8 ± 0.61 kg were used over a 132-day feeding period to determine the optimum level for substitution of concentrate with fresh sweet potato vines (SPV), having dry matter of 92%, crude protein of 19% and gross energy of 15.6 KJ/g DM for both biological and economic benefits. Five SPV substitution treatments in percentage: SPV0 as control, SPV25, SPV50, SPV75, and SPV100 were tested. The concentrate was a mixture of 78.4% wheat bran, 20.6% noug seed cake, and 1% salt with CP 20.5% and ME 2.16 MJ/kg DM. The animals took about 56 days to adapt to the SPV and recorded increasing DM intake with increasing inclusion of SPV in the ration. There were significant differences (P < 0.05) in body weight changes (ADG), body measurements and feed conversion ratio (FCR) that were lower after the recorded optimum 50% SPV substitution level. Economic analysis from the substitution treatments showed that SPV50 > SPV25 > SPV100 > SPV75 > SPV0, and 50% SPV substitution having most profitable with an average net return of 41.73 (ETB)/head. Therefore, it can be concluded that 50% SPV substitution for concentrate can be used for growing Arsi-Bale male goats with acceptable weight gain, feed intake, body measurements and economic returns.